Les gardiens du nouveau monde - Laval, Flo (France : Les films d'un jour, 2014)
Following the example of the hackers, it is a question of understanding, in our own turn, the political and economic issues at stake behind our screens. "Guardians of the new world" tells us about the emergence of a new generation of hacktivists, that must be more and more heard.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films